Cryopreservation of Human iPS Cell Aggregates in a DMSO-Free Solution—An Optimization and Comparative Study - Li, Rui; Hornberger, Kathlyn; Dutton, James R.; Hubel, Allison (Frontiers in Bioengineering and Biotechnology, 2020)
Human induced pluripotent stem cells (hiPSCs) are an important cell source for regenerative medicine products. Effective methods of preservation are critical to their clinical and commercial applications. The use of a dimethyl sulfoxide (DMSO)-free solution containing all nontoxic molecules offers an effective alternative to the conventional DMSO and alleviates pain points associated with the use of DMSO in the cryopreservation of hiPSCs. Both hiPSCs and cells differentiated from them are commonly multicellular systems, which are more sensitive to stresses of freezing and thawing than single cells. In this investigation, low-temperature Raman spectroscopy visualized freezing behaviors of hiPSC aggregates in different solutions. These aggregates exhibited sensitivity to undercooling in DMSO-containing solutions. We demonstrated the ability to replace DMSO with nontoxic molecules, improve post-thaw cell survival, and reduce sensitivity to undercooling. An accelerated optimization process capitalized on the positive synergy among multiple DMSO-free molecules, which acted in concert to influence ice formation and protect cells during freezing and thawing. A differential evolution algorithm was used to optimize the multi-variable, DMSO-free preservation protocol in 8 experiments. hiPSC aggregates frozen in the optimized solution did not exhibit the same sensitivity to undercooling as those frozen in non-optimized solutions or DMSO, indicating superior adaptability of the optimized solution to different freezing modalities and unplanned deviations. This investigation shows the importance of optimization, explains the mechanisms and advantages of a DMSO-free solution, and enables not only improved cryopreservation of hiPSCs but potentially other cell types for translational regenerative medicine.